Structural, Magnetic,and Magneto-transport Properties of NI-MN-IN based Shape memory Heusler Alloys and related Systems : - Dubey, Krishna Kant (IIT(BHU) Varanasi, 2026)
Abstract is available in the attachment.
Keywords: Material Science and technology